Is Work-Related Rumination Associated with Deficits in Executive Functioning? - Cropley, Mark; Zijlstra, Fred R. H.; Querstret, Dawn; Beck, Sarah (Frontiers in Psychology, 2016)
Abstract Work-related rumination, that is, perseverative thinking about work during leisure time, has been associated with a range of negative health and wellbeing issues. The present paper examined the association between work-related rumination and cognitive processes centred around the theoretical construct of executive functioning. Executive functioning is an umbrella term for high level cognitive processes such as planning, working memory, inhibition, mental flexibility; and it underlies how people manage and regulate their goal directed behaviour. Three studies are reported. Study I, reports the results of a cross-sectional study of 240 employees, and demonstrates significant correlations between work-related rumination and three proxy measures of executive functioning: cognitive failures (.33), cognitive flexibility (-.24) and situational awareness at work (-.28). Study II (n = 939), expands on the findings from study 1 and demonstrates that workers reporting medium and high work-related rumination were 2.8 and 5 times, respectively, more likely to report cognitive failures relative to low ruminators. High ruminators also demonstrated greater difficulties with ‘lapses of attention’ (OR = 4.8), ‘lack of focus of attention’ (OR = 3.4), and ‘absent mindedness’ (OR = 4.3). The final study, examined the association between work-related rumination and executive functioning using interview data from 2460 full time workers. Workers were divided into tertiles low, medium and high. The findings showed that high work-related rumination was associated with deficits in starting (OR = 2.3) and finishing projects (OR = 2.4), fidgeting (OR = 1.9), memory (OR = 2.2), pursuing tasks in order (OR = 1.8), and feeling compelled to do things (OR = 2.0). It was argued that work-related rumination may not be related to work demands per se, but appears to be an executive functioning/control issue. Such findings are important for the design and delivery of intervention programmes aimed at helping people to switch off and unwind from work.